The Performance of Students in the Practical Evaluation of Muscle Recognition in Natural and Artificial Anatomical Parts - , João Francisco Severo-Santos (Archives of Current Research International, 2023)
Learning human anatomy can be challenging for Physical Education and Medicine students. Large volume of information, technical terminology, difficulty in visualizing 3D structures, lack of practice and emotional pressure are some challenges faced by students. However, the study of muscle anatomy is as important for physicians as it is for physical educators, albeit for different main reasons. In this study, the objective was to verify if there are differences in the performance of medical and physical education students in practical tests of recognition of muscular structures in natural and artificial anatomical parts. From approximately 126 muscles of the upper and lower limbs and their girdles, 20 structures were drawn (10 in natural pieces and 10 in artificial pieces). The notes and class notebook records of 86 physical education students and 103 medical students from two public universities were compared, considering that there were no differences between the evaluation methods and the professors in charge. It was found that, despite substantial differences in the socioeconomic profile of each course, physical education students were significantly better at recognizing muscle structures. However, this result was dependent on the better performance of physical education students in the evaluation of artificial parts. The students' performance was lower, much more variable and similar between the groups in the evaluation of the natural pieces. Such results suggest the need for greater contact and manipulation, especially of medicine, in cadaver pieces.